1983
DOI: 10.1021/bi00277a041
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of metal cations bound to membranes and extracted lipopolysaccharide of Escherichia coli

Abstract: Inductively coupled plasma emission spectroscopy was used to quantitate the metal cations bound to outer and cytoplasmic membranes and to extracted lipopolysaccharide from several Escherichia coli K12 strains. The outer membrane was found to be enriched in both calcium and magnesium relative to the cytoplasmic membrane. Both membranes contained significant levels of iron, aluminum, and zinc. The multivalent cation content of the lipopolysaccharide resembled that of the intact outer membrane. Lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
3
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 30 publications
6
118
3
1
Order By: Relevance
“…From the results they postulated that Mg bound to the LPS was divided into two types by its strength of binding (1). In contrast, we found that, as in the case of the LPS from K. pneumoniae strain LEN-111, Mg bound to the LPS from E. coli K-12 strain JE1011 could be removed almost completely and Ca was significantly decreased with electrodialysis (5).…”
Section: Discussionmentioning
confidence: 86%
“…From the results they postulated that Mg bound to the LPS was divided into two types by its strength of binding (1). In contrast, we found that, as in the case of the LPS from K. pneumoniae strain LEN-111, Mg bound to the LPS from E. coli K-12 strain JE1011 could be removed almost completely and Ca was significantly decreased with electrodialysis (5).…”
Section: Discussionmentioning
confidence: 86%
“…In Gram-negative bacteria such as E. coli, magnesium is involved in stabilization of membrane phospholipids, lipopolysaccharide, polyphosphate compounds like DNA and RNA, and the ribosome (11)(12)(13). Magnesium is also required to make ATP biologically active and participates in catalysis of certain enzymatic reactions through either direct or indirect mechanisms (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The ladderlike banding patterns represent molecules with increasing numbers of 0-antigen repeat units (20,24,45 1, 2, 3, and X were separated on Sephadex G-200, dialyzed, and lyophilized as described in Materials and Methods and suspended in distilled water to a final concentration of 10 mg/ml. In the top row, 10 ,ug of each sample was applied on the nitrocellulose strip, and subsequent rows were spotted with an equal volume of 10-fold serially diluted samples. The sample spots were dried, and the nitrocellulose was either reacted with monoclonal anti-503 antibody and developed as described in Materials and Methods (A) or washed with 10 mM Tris-150 mM NaCl (pH 7.0) and reacted with the silver stain as indicated in Materials and Methods for polyacrylamide gels (B).…”
Section: Discussionmentioning
confidence: 99%
“…Assays for amino sugars (17), heptose (59), and 2-keto-3-deoxyoctulosonic acid (KDO) (28) were performed as described previously except when noted. Phosphate analyses were performed by using either a colorimetric assay (1) or inductively coupled plasma emission spectroscopy (10). Protein concentrations were estimated by the Pierce BCA protein assay (Pierce Chemical Co., Rockford, Ill.) with bovine serum albumin as the standard.…”
Section: Methodsmentioning
confidence: 99%